IL‐18: A potential inflammation biomarker in Wiskott–Aldrich syndrome. Issue 5 (5th February 2021) - Rivers, Elizabeth; Hong, Ying; Bajaj‐Elliott, Mona; Worth, Austen; Thrasher, Adrian J.
Abstract : Analysis of serum cytokine levels in Wiskott–Aldrich syndrome patients pre‐ and post‐ treatment reveals IL‐18 as a stable and reliable marker of inflammation. Definitive stem cell treatment with good myeloid correction correlates with resolution of inflammation and reduction of circulating IL‐18, highlighting the importance of actin cytoskeletal regulation of myeloid cells in control of inflammation.